Strategi Manajemen Guru PAI dalam Menghadapi Transformasi Digital: Tantangan dan Sistem Pendidikan Islam di Indonesia - Apriyani, Hikma; Yanti, Yuli; Muzzeki, Muzzeki; Ajir, Ikhtiar Cahya; Anwar, Choirul; Anwar, Syaiful; Dacholfany, Muhammad Ihsan (DIMAR: Jurnal Pendidikan Islam, 2025)
Islamic Religious Education (PAI) teachers in Indonesia face both challenges and opportunities in adapting to the rapid digital transformation in education. The integration of digital technology in Islamic education raises concerns regarding its alignment with Islamic values, disparities in digital literacy, resistance to change, and limited technological infrastructure. Previous studies have highlighted these challenges but have not comprehensively explored effective strategies for managing digital adaptation while preserving the integrity of Islamic teachings. This study employs a descriptive qualitative approach, utilizing interviews, observations, and document analysis involving PAI teachers from various Islamic educational institutions in Indonesia. The findings indicate that successful adaptation to digital transformation requires structured management strategies, including continuous professional development, contextual integration of Islamic values into digital learning, collaborative learning networks, and the development of well-curated digital content. Furthermore, this research proposes a digital-based Islamic education model that emphasizes institutional support, structured technology training for teachers, and the development of Islamic digital learning platforms. The study concludes that the success of digital transformation in Islamic education depends on the collaboration between teachers, educational institutions, and policymakers to ensure that digital learning remains effective and aligned with Islamic educational principles.